Home-School Partnership in Germany: Expectations, Experiences and Current Challenges - Angelika Paseka; Dagmar Killus (University of Bologna, 2022)
The paper focuses on parents and parental involvement in Germany as well as the challenges which became visible during the COVID-19 pandemic. As has been the case in many other countries, the notion of parents as partners, is the focus of normative discussion about how to engage with parents. However, looking at the role actually played by parents in school settings, and the way school institutions interact with them, it can be seen that there is a difference. This paper describes: first, how the different roles that parents played were understood, prior to the pandemic; secondly, the part played by parents while schools were closed as a result of the pandemic; and thirdly, the strengthening of home-school partnerships in Germany, contrasting this with the roles parents take within them. The results are critically assessed under the broader perspective of de-familialism versus familialism.